Long COVID: challenges and complications – a systematic review - SHANNAWAZ, Mohd; GUPTA, Shikhar; SHAH, Nikita; RATHI, Isha; SAEED, Shazina; CHANDRA, Amrish; THAKUR, Ruchi (One Health & Risk Management, 2025)
Introduction. Long COVID, a condition that follows the acute phase of COVID-19, presents diverse clinical, psychological, and socioeconomic challenges, with complications such as fatigue, cognitive impairment, musculoskeletal issues, and mental health conditions. Despite its impact, the burden of long COVID symptoms on public health remains underexplored. This systematic review synthesizes current evidence on the complications and challenges of long COVID to inform healthcare providers and policymakers.Material and methods. A systematic literature search was conducted using PubMed and Scopus databases for studies published between January 2020 and August 2024. Articles were selected based on inclusion criteria, including both qualitative and quantitative studies. The review adhered to PRISMA guidelines, and the risk of bias was assessed using the NIHR risk-of-bias tool.Results. A total of 23 studies from 17 countries were included. Findings presented a multifaceted burden, with physical symptoms such as fatigue (5.5%–84.4%), brain fog (67%), headaches (5%–76.6%) and sleep disturbances (22%–60.9%). Psychological impacts were also prominent, with anxiety and depression frequently reported. Socioeconomic consequences were substantial, with up to 42.3% of individuals unable to return to work.Conclusions. Long COVID poses significant challenges to individuals and public health systems. Despite emerging insights, there are substantial gaps in understanding and managing long COVID, underscoring the need for further research and comprehensive healthcare strategies.